The Role of Religious Values and Beliefs in Shaping Mental Health and Disorders - Beata Pastwa-Wojciechowska; Iwona Grzegorzewska; Mirella Wojciechowska (Religions, 2021)
Mental health is an area of continuous analysis, both in the context of understanding increasingly precise diagnostic criteria and the impact of therapeutic methods. In addition to these well-established directions of analysis and search, psychology tries to explore the factors that bring us closer to understanding the mechanisms of the genesis and development of disorders, as well as their importance in psychoeducation or therapy. The increased interest in issues of spirituality/religion observed in recent years translates into the pursuit to explore the relationship between religion/spirituality and health. This article reviews research into the ability of religion and spirituality to benefit or harm the mental health of believers. We also examine the mechanism of developing religious delusions in schizophrenia. Religion and spirituality can promote or damage mental health. This potential demands an increased awareness of religious matters by mental health practitioners, as well as ongoing attention in clinical psychology research.